2018
DOI: 10.1371/journal.pone.0195444
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal behavioural responses of wild cattle to tropical forest degradation

Abstract: Identifying the consequences of tropical forest degradation is essential to mitigate its effects upon forest fauna. Large forest-dwelling mammals are often highly sensitive to environmental perturbation through processes such as fragmentation, simplification of habitat structure, and abiotic changes including increased temperatures where the canopy is cleared. Whilst previous work has focused upon species richness and rarity in logged forest, few look at spatial and temporal behavioural responses to forest deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
(75 reference statements)
1
0
0
Order By: Relevance
“…With the substantial contraction in cattle activity, the change in forest coverage from 1997 to 2013 showed that forests regenerated in the areas formerly dedicated to pastures, beginning with the recovery of small fragments. These results of forest fragmentation obtained are like those reported by Gardner et al (2018) and Laurance et al (2006).…”
Section: Discussionsupporting
confidence: 91%
“…With the substantial contraction in cattle activity, the change in forest coverage from 1997 to 2013 showed that forests regenerated in the areas formerly dedicated to pastures, beginning with the recovery of small fragments. These results of forest fragmentation obtained are like those reported by Gardner et al (2018) and Laurance et al (2006).…”
Section: Discussionsupporting
confidence: 91%